2021
DOI: 10.1038/s41467-021-21463-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibody affinity maturation and plasma IgA associate with clinical outcome in hospitalized COVID-19 patients

Abstract: Hospitalized COVID-19 patients often present with a large spectrum of clinical symptoms. There is a critical need to better understand the immune responses to SARS-CoV-2 that lead to either resolution or exacerbation of the clinical disease. Here, we examine longitudinal plasma samples from hospitalized COVID-19 patients with differential clinical outcome. We perform immune-repertoire analysis including cytokine, hACE2-receptor inhibition, neutralization titers, antibody epitope repertoire, antibody kinetics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 34 publications
8
117
1
Order By: Relevance
“…In the case of COVID-19, however, their roles remain less defined, e.g. the predictive value of neutralisation with regard to disease outcome [ 40 , 55 ].…”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of COVID-19, however, their roles remain less defined, e.g. the predictive value of neutralisation with regard to disease outcome [ 40 , 55 ].…”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%
“…The absence of NAb response early after disease onset showed the strongest correlation with mortality and delayed viral control—more so than the difference in NAb titre. Almost all patients develop NAb by week 4 of infection, and severely ill patients exhibit higher peak, faster and stronger NAb titres compared to mild cases [ 40 , 55 , 56 ]. Hospitalised patients harbour greater NAb titres than mildly symptomatic and asymptomatic patients whose titres were below the detection limit in half of the cases [ 57 ].…”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%
“…Recently, we showed that SARS-CoV-2 spike GFPDL can recognize both linear, conformational and neutralizing epitopes in the post-vaccination sera of rabbits and post-SARS-CoV-2 infection sera in adults and the elderly. Adsorption of immune sera with the SARS-CoV-2-S-GFPDL removed >90% of the anti-spike binding antibody in postinfection human sera (Ravichandran et al, 2020(Ravichandran et al, , 2021Tang et al, 2021).…”
Section: Sars-cov-2 Spike Antibody Epitope Repertoires Of Six Hcov-2ig Batchesmentioning
confidence: 99%
“…A gIII display-based phage vector, fSK-9-3, was used where the desired polypeptide can be displayed on the surface of the phage as a gIII-fusion protein. Purified DNA containing spike gene was digested with DNaseI to obtain gene fragments of 50-1,500 bp size range (18-500 amino acids) and used for GFPDL construction (Khurana et al, 2020;Ravichandran et al, 2020;Tang et al, 2021).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Neutralisation titres were measured using a pseudovirus neutralisation assay (PsVNA) as described previously. 6 No SARS-CoV-2 neutralising antibodies were detected in plasma at 4 weeks after the second mRNA-1273 vaccination. In the same assay, age-matched (65-77 years old) immunocompetent individuals (healthcare workers who were not on any immunosuppressive drugs and vaccinated with two doses of mRNA-1273 SARS-CoV-2 vaccine in Maryland) generated neutralising antibody titres (PsVNA50: 50% reduction in neutralisation titres) ranging between 1:451 and 1:3293 against the WA-1 strain following mRNA-1273 vaccination.…”
mentioning
confidence: 96%